Anti-inflammatory α-Melanocyte-Stimulating Hormone Protects Retina After Ischemia/Reperfusion Injury in Type I Diabetes - Goit, Rajesh Kumar; Taylor, Andrew W.; Lo, Amy C. Y. (Frontiers in Neuroscience, 2022)
Retinal ischemia/reperfusion (I/R) occurs in many ocular diseases and it leads to neuronal damage and visual complications. Retinal I/R injury is common in diabetic retinopathy, which as a result of hyperglycemia damages the retina and can cause blindness if left untreated. Inflammation is a major contributing factor for the pathogenesis of I/R injury. α-Melanocyte stimulating hormone (α-MSH) is an anti-inflammatory peptide hormone that has displayed protective effects against I/R-induced organ damages. Here, we aimed to investigate the protective role of α-MSH on I/R-induced retinal damage using hyperglycemic C57BL/6J Ins2Akita/+ mice. Experimental I/R injury was induced by blocking the right middle cerebral artery (MCA) for 2 h followed by 2 h or 22 h of reperfusion using the intraluminal method. Since ophthalmic artery originates proximal to the origin of the MCA, the filament also blocked blood supply to the retina. Upon treatment with α-MSH at 1 h after ischemia and 1 h after reperfusion, animals displayed significantly improvement in b-wave amplitude. α-MSH also prevented I/R-induced histological alterations and inhibited the development of retinal swelling. Loss of retinal ganglion cells, Müller cells activation as well as oxidative and nitrative stress were significantly attenuated in the α-MSH-treated retinae. Levels of interleukin 10 was significantly increased. Moreover, gene expression of glutamate aspartate transporter 1, monocarboxylate transporter (MCT) 1 and MCT-2 were significantly higher after α-MSH administration. In conclusion, α-MSH mitigates the severity of I/R-induced retinal damage under hyperglycemic condition in maintaining retinal structural and functional integrities. These beneficial effects of α-MSH may have important therapeutic implications against retinal I/R injury under hyperglycemic condition.